Potential use of name data networking in vehicle-to-vehicle communication - Elbreiki, Walid; Habbal, Adib M. Monzer; Hassan, Suhaidi; Che Mohamed Arif, Ahmad Suki (Asian Research Publishing Network (ARPN), 2015)
Researchers have proposed several content dissemination techniques for addressing the massive growth in content exchange.Named Data Networking (NDN) is one of the novel ideas in which networks use named data for content dissemination instead of host identities.In NDN, the content itself is presented in the network layer based on user interests.The use of NDN in Vehicle-to-Vehicle (V2V) communication has numerous potential due to the advantages of named based data retrieval against host based data searching.This paper presents an in-depth review of the potential uses of NDN in V2V environment with special emphasis on their advantages and disadvantages.The paper also provides future research direction that could be undertaken on the subject.